Kepemimpinan Kepala Sekolah Dasar di Kota Lubuklinggau dalam Meningkatkan Mutu Sekolah di Era Digital - Ahmad Gawdy Prananosa; Tamri Tamri; Rahmat Sudrajat (Journal Of Administration and Educational Management (ALIGNMENT), 2026)
This study aims to analyze the leadership of elementary school principals in Lubuklinggau City in improving school quality in the digital era. The research method used was a qualitative approach with phenomenology, with research subjects including the principal, teachers, school staff, parents, and the school committee. Data collection techniques were conducted through observation, interviews, and documentation, while data analysis employed the Miles and Huberman interactive model, which includes data reduction, data presentation, and drawing conclusions. The results indicate that principal leadership in improving school quality in the digital era is achieved through understanding the challenges and opportunities of digitalization, strengthening principals' digital competencies, encouraging teachers to utilize technology in learning, providing adequate digital facilities and infrastructure, building collaboration among teachers in developing digital materials, ensuring the security and privacy of school data, fostering a positive digital culture, and establishing policies for the wise use of digital devices. The conclusions of this study confirm that adaptive, innovative, and digital-based principal leadership plays a strategic role in improving school quality through learning management, school management, and strengthening digital culture and security in elementary schools.   Keywords: Principal Leadership, School Quality, Digital Era, Digital Competence, Digital Culture